2013
DOI: 10.1002/jaba.39
|View full text |Cite
|
Sign up to set email alerts
|

On the Representativeness of Behavior Observation Samples in Classrooms

Abstract: School consultants who rely on direct observation typically conduct observational samples (e.g., 1 30-min observation per day) with the hopes that the sample is representative of performance during the remainder of the day, but the representativeness of these samples is unclear. In the current study, we recorded the problem behavior of 3 referred students for 4 consecutive school days between 9:30 a.m. and 2:30 p.m. using duration recording in consecutive 10-min sessions. We then culled 10-min, 20-min, 30-min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…However, a small absolute difference (e.g., when a behavior is recorded as not occurring, or 0, but occurs during 1% of the timeof-interest, resulting in an absolute difference of 1%) may not sufficiently reflect true duration even though the absolute difference would fall on a AE1% absolute accuracy limit. We agree with the views of Tiger et al (2013) that acceptable error is likely to be judged according to the purposes of data collection, and thus we suggest that there are merits to evaluating both absolute and relative errors. Perhaps acceptable error varies with overall behavioral duration (e.g., absolute error of AE5% may be acceptable for behaviors that occur for 50% of the week but not for those that occur for 5% of the week).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, a small absolute difference (e.g., when a behavior is recorded as not occurring, or 0, but occurs during 1% of the timeof-interest, resulting in an absolute difference of 1%) may not sufficiently reflect true duration even though the absolute difference would fall on a AE1% absolute accuracy limit. We agree with the views of Tiger et al (2013) that acceptable error is likely to be judged according to the purposes of data collection, and thus we suggest that there are merits to evaluating both absolute and relative errors. Perhaps acceptable error varies with overall behavioral duration (e.g., absolute error of AE5% may be acceptable for behaviors that occur for 50% of the week but not for those that occur for 5% of the week).…”
Section: Discussionsupporting
confidence: 82%
“…Equation 1 calculates the required numbers of observations based on relative error (i.e., error as a percentage of the duration), which results in minute absolute-error margins for behaviors that occur for 10% or less of the week (e.g., when true duration is 1%, AE5% absolute error would result in margins of 0.95% and 1.05%). Tiger et al (2013) suggested that as Mudford et al (1990) reported relative error, small errors in measuring low-duration behaviors were amplified. Tiger et al therefore suggested that reporting absolute error allows for fairer comparisons of errors for high-and low-duration behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using an Every Fifth PAC method, the data suggest that longer duration observations (e.g., 60 min) do not confer any substantial benefit over shorter duration (e.g., 10 min) observations. These results add to the literature suggesting that shorter duration observations may yield sufficiently representative estimates of behavior (e.g., Tiger et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…However, the number and length of observations required to obtain data related to the behavior of interest is not easily predicted. For example, Tiger et al () conducted 5‐hr observations of problem behavior exhibited by three children across four consecutive school days. In cases where behavior occurred with low variability, briefer observations (e.g., 10 min) were sufficient for obtaining an accurate sample of behavior.…”
Section: Discussionmentioning
confidence: 99%